2012
DOI: 10.1016/j.reprotox.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive effects in F1 adult females exposed in utero to moderate to high doses of mono-2-ethylhexylphthalate (MEHP)

Abstract: Phthalates are widely used as plasticizers in everyday products. Yet, studies on the effects of phthalates on female reproductive health are limited. In this study, pregnant C57/Bl6 mice were exposed via oral gavage to corn oil, 100, 500, or 1000mg/kg MEHP from gestational days 17–19. Reproductive lifespan was decreased by one month in the highest F1 exposure group (9.8±0.4 versus 11.1±0.6 months in control F1 females). F1 females exhibited delayed estrous onset at the two higher exposures and prolonged estrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 36 publications
3
53
0
1
Order By: Relevance
“…Additionally, similar to previous phthalate work (28) vaginal openings in female BBP mice were significantly delayed compared to control mice (p=0.001; Figure 3b). …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, similar to previous phthalate work (28) vaginal openings in female BBP mice were significantly delayed compared to control mice (p=0.001; Figure 3b). …”
Section: Resultssupporting
confidence: 88%
“…Similar to the male mice, in the female mice we observed a decrease in estradiol as well as a delayed vaginal opening, which is an index associated with disrupted endocrine functioning (28). Associated with these alterations was a significant difference in distance and duration of exercise, but not speed in the BBP mice, confirming our hypothesis that exposure to BBP will alter physical activity.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies have shown that DEHP and MEHP accelerate primordial follicle recruitment in vivo [35,79,80]. The limitation of these studies is that they did not determine if these chemicals act directly on the ovary to elicit this response.…”
Section: Discussionmentioning
confidence: 96%
“…However, the effects of prenatal phthalate exposure on female reproduction in the offspring are less extensively studied. Published studies have shown that gestational exposure to DEHP affects folliculogenesis [17], reduces oocyte quality [18], decreases steroidogenic capacity [18, 19], delays puberty [19], and decreases fertility [17, 18]. …”
Section: Introductionmentioning
confidence: 99%